Novel low viscosity ammonium-based ionic liquids with carboxylate anions: Synthesis, characterization, and thermophysical properties - M.I., Abdul Mutalib (2017)
A new group of low viscosity hydrophobic trioctylammonium-based protic ionic liquids (PILs) with 2-naphthoate, 4-tert-butylbenzoate, 2-hexyldecanoate, and 4-phenylbutanoate anions were synthesized. All the synthesized PILs were liquids at room temperature. The PILs were characterized using nuclear magnetic resonance, elemental analysis, and Fourier transform infrared spectroscopy.